Dukungan Sosial bagi Penderita Disfungsional untuk Penguatan Kesehatan Mental: Studi Syarah Hadis dengan Pendekatan Psikologi Islam - Muhamad Azhan Azhari (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss the hadith about mental health with a religious psychology approach. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this study include a general view of mental health, hadith on mental health, and mental health with a religious psychology approach. The conclusion of this study is that mental health is related to psychotherapy through the practice of worship, in the sense that all kinds of teachings and rituals in religion can help heal mental disorders and religious teachings keep away from negative solutions. This research is expected to have enrichment for health and Islamic knowledge.